Quality of life among older people in inland vs. coastal Croatia: follow-up study on chronic diseases - Pavlović, Mladen (Array, 2008)
Introduction: The CASP-19 questionnaire is a standard instrument for assessing quality of life in older people that has been designed in the UK. Subjects are asked to rate the degree of their agreement with a number of statements about their quality of life (1-3). Objective: To investigate different predictors of quality of life in mobile non-institutionalised aged population in inland/coastal Croatia. Sample and methods: Participants in the study on chronic diseases - follow-up in the years 1969, 1972, 1982 and 2006. Sample: 213 women and 177 men, volunteers from three coastal areas: island of Vis (rural area), city of Split (urban mainland), and Omis (mainland suburbia) and three inland areas: city of Zagreb (metropolitan area) with two urban districts (Centre and Western district) and Virovitica (rural). Age range: 70-92 years ; 70-74 years, cohort 1, 75-92 years, cohort 2. Year of questionnaire administration: 2006 and 2007. Instrument: CASP-19 questionnaire contains quality of life assessment indicators for elderly people through conceptual domains: Control, Autonomy, Pleasure and Self-realization. Statistics: ANOVA. Results: We found statistical differences in the following domain scores: Autonomy - between Zagreb-Centre and Virovitica ; Pleasure - between Virovitica and Omis ; Self-realization - statistically significant difference (p<0.05) between the cohort 1 and cohort 2 between Omis and Vis, and between Zagreb-Western district and Omis. No statistically significant differences in Autonomy and Pleasure were observed between cohorts 1 and cohort 2. Conclusion: Our results show differences in quality of life indicators between rural/urban and inland/coastal elderly population as well as difficulties in domains Self-realization and Control in the senior cohort (cohort 2). References: 1] Wiggins RD et al Ageing Soc 2004 ; 24: 693-708. 2] Hyde M et al Aging Ment Health 2003 ; 7: 186-94. 3] Pavlovic M, Ugrenovic Z, Mimica M. Coll Antropol 1995 ; 19: 209-14.